A review of potential impacts of submarine power cables on the marine environment: Knowledge gaps, recommendations and future directions. (November 2018) - Taormina, Bastien; Bald, Juan; Want, Andrew; Thouzeau, Gérard; Lejart, Morgane; Desroy, Nicolas; Carlier, Antoine
Abstract: Submarine power cables (SPC) have been in use since the mid-19th century, but environmental concerns about them are much more recent. With the development of marine renewable energy technologies, it is vital to understand their potential impacts. The commissioning of SPC may temporarily or permanently impact the marine environment through habitat damage or loss, noise, chemical pollution, heat and electromagnetic field emissions, risk of entanglement, introduction of artificial substrates, and the creation of reserve effects. While growing numbers of scientific publications focus on impacts of the marine energy harnessing devices, data on impacts of associated power connections such as SPC are scarce and knowledge gaps persist. The present study (1) examines the different categories of potential ecological effects of SPC during installation, operation and decommissioning phases and hierarchizes these types of interactions according to their ecological relevance and existing scientific knowledge, (2) identifies the main knowledge gaps and needs for research, and (3) sets recommendations for better monitoring and mitigation of the most significant impacts. Overall, ecological impacts associated with SPC can be considered weak or moderate, although many uncertainties remain, particularly concerning electromagnetic effects. Graphical abstract: fx1 Highlights: The use of submarine power cables will increase due to the growth of the marine renewable energy sector. Installation increases noise, pollution, turbidity and physical disturbance. Operation produces electromagnetic fields, heat, entanglement risk, pollution and reef/reserve effects. Overall impacts on ecosystems are considered minor or short-term. Uncertainties remain, particularly concerning the impacts of electromagnetic fields.